Artificial Intelligence (AI) as a Predictive Tool to Anticipate Future HR Management Needs - Muliarta, I Nengah (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2024)
Artificial intelligence (AI) in human resource management (HR) opens up opportunities for increased effectiveness and efficiency in various tasks, such as training, recruitment, and performance management. The purpose of this article is to look at and analyze how AI can serve as a predictive tool to anticipate future HR needs. This includes identifying the problems organizations face when implementing AI and providing solutions. The role of AI as a predictor tool in determining future human resource needs is discussed in this article through a literature review. This methodology aims to provide a comprehensive understanding of how AI can be used to predict future needs and work styles. As a result, AI has the potential to be a predictive tool for HR development, as it can assist organizations in designing the right training programs, managing employee careers, and improving performance analysis. Including the ability to analyze data and provide valuable insights.